2010
DOI: 10.2478/s11756-010-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation in natural populations of Lotus corniculatus in association to geographical parameters of collecting sites

Abstract: Phenotypic variation and association between morphologic traits and geographic characteristics (latitude, longitude and elevation) were investigated for fifteen wild birdsfoot trefoil (Lotus corniculatus L.) populations collected from diverse natural stands in Slovakia. Considerable variation between populations was observed for morphological characteristics. According to principal component analysis, the attributes that appeared to be the major sources of diversity between these populations were growth habit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
3
8
1
Order By: Relevance
“…Taylor and Smith (1995) and Dias et al (2008) in white clover (Trifolium repens L.) reported that early-flowering populations were predominant at lower latitude. Similar patterns of association among geographical characteristics have been reported by Greene et al (2004) for red clover and Drobna (2010) for Lotus. ** Significant at p = 0.01.…”
Section: Agro-morphological Analysissupporting
confidence: 74%
“…Taylor and Smith (1995) and Dias et al (2008) in white clover (Trifolium repens L.) reported that early-flowering populations were predominant at lower latitude. Similar patterns of association among geographical characteristics have been reported by Greene et al (2004) for red clover and Drobna (2010) for Lotus. ** Significant at p = 0.01.…”
Section: Agro-morphological Analysissupporting
confidence: 74%
“…As reported by Drobná (2010), morphological and agronomical variations were strongly associated with altitude of the collecting-site. The traits of stem, leaflet length, number of seed per pod, herbage yield, leaf to stem ratio and 1000 seed weight were influenced highly by altitude ( Table 2).…”
Section: Population Descriptionsupporting
confidence: 64%
“…These results indicate that there was a decrease in present frequency of NBT with increasing altitude. Although it has been reported that NBT may be adapted to all ranges of altitude (Davis 1970;Drobná 2010), based on findings of present study and some other studies Drobná 2010), it can be said that NBT better adapted to lowlands.…”
Section: Distribution Regarding To Altitudecontrasting
confidence: 44%
“…The plant habit is mainly erect or sub-erect; however, some accessions have a more prostrate or rosette habit and most accessions will die back to a short prostrate plant over the winter months. The morphological plasticity of sainfoin adds to difficulties in characterizing varieties, malleability contributes to its ability to cold stress during winter and early spring (Frame et al ., 1998; Seker et al ., 2003; Drobná, 2010; Hayot Carbonero, 2011b).…”
Section: Botanical Description Of Sainfoinmentioning
confidence: 99%